EKSPERIMEN PEMBUATAN KUE SEMPRONG SUBSTITUSI SANTAN DENGAN KOPI ESPRESSO SEBAGAI ALTERNATIF VARIAN RASA - Rosie Oktavia Puspita Rini; Muhamad Rafi Abdul Malik (PUSLITABMAS - BATAM TOURISM POLYTECNIC, 2023)
The new taste presented by the addition of espresso coffee in making semprong cakes can also be an alternative for the community to enjoy semprong cakes. This research is an experimental study of making semprong cakes with the addition of espresso coffee levels of 30, 60 and 90. Experiments were carried out on 15 trained panelists and 20 untrained panelists. Based on the results of the hedonic quality test, the results obtained were that as many as 20 people, starting from 20 combined panelists, 10 trained panelists, and 10 untrained panelists stated that the coconut milk substitute semprong cake experiment with espresso coffee had significant differences in the color aspect. aroma, texture, and taste. Based on the results of the hedonic test, it was found that as many as 15 people including 15 combined panelists, 5 trained panelists, and 10 untrained panelists stated that they preferred color, aroma, texture, and taste in the sample. A which has a dark brown color, coffee aroma, very crunchy texture, and a sweet and slightly bitter taste.